SELF EFFICACY MEMEDIASI PENGARUH KONDISI SOSIAL EKONOMI ORANG TUA DAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR EKONOMI - Puspitasari, Zenni; Margunani, Margunani (Universitas Negeri Semarang, 2017)
The purpose of this study is to know the role of self-efficacy in mediate the influence of socio-economic condition of parents and school environment on the learning outcomes. The population of this study was all of XI IPS students in SMA Negeri 1 Godong in the academic year of 2016/2017 by 110 students. Methods of data collection using questionnaires and documentation. Methods of data analysis were descriptive analysis, path analysis, and sobel test. The results showed that there is positive and significant influence of socio-economic condition of the parents on the economic learning outcomes of the students. There is positive and significant impact of School Environment on the economic learning outcomes. There is positive and significant influence of Self Efficacy on the economic learning outcomes of the students. There is positive and significant influence of the socio-economic condition of the parents on the self-efficacy. There is positive and significant influence of school environment on self-efficacy of the students. There is indirect effect of the socio-economic condition of the parents on the economic learning outcomes through self-efficacy as an intervening variable. There is indirect effect of the school environment on economic learning outcomes through self-efficacy as an intervening variable.